Forensic evidence management :from the crime scene to the courtroom - AshrafMozayani,Ed; Parish-Fisher, Casie L,Ed (CRC, 2018)
"Evidence management has become a crucial component for the law enforcement community. I truly believe this book is essential in assisting criminal investigators and a valuable resource for managing evidence."—Jeremiah Sullivan, Chairman, Board of Directors, Texas Division of the International Association for Identification; Senior Crime Scene Specialist (Retired). Austin Police Department